Technology Independent Video Streaming in Mobile Phones (TIVSMoPh) - Briones, Khristine Anne
With the advancement of mobile technology, different means of Internet connection are now available for the consumers. These different means of connection offer varying speeds, and among them, WLAN is the fastest. However, along with its wireless nature and its tolerance to user's mobility, varying bandwidth cannot be avoided. Video streaming is a very attractive application since it provides audio-visual entertainment. It has been a trend nowadays since it enables the users to start viewing a video without downloading the entire file. For this to be possible, streaming applications demand memory and an uninterrupted bandwidth network. Video streaming in mobile phones deals with two key issues that affect its performance. The first one is the phone memory since it has restricted resources as compared to other mobile devices. The second issue is the Internet connection which now varies from 2G, 3G and WLAN. Switching between networks could lead to a loss of connection during video streaming. Also, network congestion could lead to variation in network bandwidth, and in turn could lead to choppy video streaming. This research aims to address these issues by creating an application that automatically adapts to the variation in network bandwidth. An efficient buffering system will be implemented so that video playback will be as smooth as possible. The model that we used in implementing the system is the client-server architecture of computer networks. The components are connected through User Data Protocol (UDP) and uses WLAN to connect. The performance of the system is tested on the basis of delay time and choppiness where the buffer and packet sizes are varied. Results show that the system was able to provide a continuous service even during network disconnection, and was able to reduce jitter through the use of the buffering system.